Features of the professional training of future technicians and mechanics in college - STADIYCHUK, Iryna; KUBITCKIY, Sergiy (Journal of Education, Technology and Computer Science, 2013)
The article presents the characteristics of professional training of futuretechnicians and mechanics in Agrotechnical Colleges. Substantiated leadingprofessional functions of future technicians and mechanics and the correspondingto them professional skills. It is shown specific formation of professionalcompetences of future technicians and mechanics